Outcomes of rectangular 3-snip punctoplasty in acquired punctal stenosis: is there a need to be minimally invasive? - Ali, M J (Eye (Lond), 2015)
AIM: To report the clinical profiles of acquired punctal stenosis and outcomes with rectangular 3-snip punctoplasty. METHODS: Retrospective chart review of all patients who underwent rectangular 3-snip punctoplasty, over a 3-year period from a single surgeon's (MJA) database was performed. Data retrieved include demographics, symptomatology, prior interventions, grades of punctal stenosis, associated ocular findings, and outcomes. A minimum follow-up of 6 months following punctoplasty was considered for analysis. Success was defined as clearance of dye on functional dye disappearance test and resolution of symptoms. RESULTS: One hundred and forty five puncta of 87 eyes of 56 patients were studied. The mean age at presentations was 52 years. Puncta (71.7% 104/145) were of grade 2 size. Epiphora was the commonest presenting symptom noted in 94.3% (82/87) of the eyes. At a minimum follow-up of 6 months, complete resolution of symptoms was achieved in 74.7% (65/87) of eyes. Eight out of 87 eyes (9.1%) failed to show any improvement secondary to lacrimal obstructions distal to the puncta. Five out of 87 (5.7%) eyes showed punctal restenosis whereas 10.3% (9/87) of the eyes had functional epiphora post punctoplasty. CONCLUSION: Puncta of grade 2 size were the most common in this series. Although rectangular 3-snip punctoplasty is an effective and safe procedure for majority of grades 1 and 2 of acquired punctal stenosis, a higher percentages of functional epiphora and punctal restenosis in the remaining patients should propel further investigations into developing nonincisional, minimally invasive alternatives.